PENGETAHUAN IBU HAMIL TENTANG PENCEGAHAN ANEMIA SELAMA KEHAMILAN - Dina Indarsita; yufdel; Nabila; Elfina (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Background: Anemia in pregnant women is when in the first and third trimesters of pregnancy the hemoglobin level is <11 gr/dl or in the second trimester of pregnancy the hemoglobin level is <10.5 gr/dl. Anemia in pregnancy can be caused by iron deficiency and treatment of anemia caused by iron deficiency can be overcome easily and cheaply. Objective: The purpose of this study was to determine the knowledge and attitudes of pregnant women toward preventing anemia during pregnancy at the Padang Bulan Community Health Center. Method: This study used a descriptive method with a cross-sectional research design using a purposive sampling technique. The population in this study were all pregnant women who underwent Antenatal Care examinations totaling 245 respondents, with a sample of 38 people in the study. The measuring instrument for this study was a questionnaire with data collection using a frequency distribution. Results: The results showed that pregnant women with good knowledge about preventing anemia were 18 people (47.4%).